Relationship Between Strategic Orientation, Service Innovation and Its Impact on Market Performance - Maria; Shah, Syed Moin-ud-Din (iRASD Journal of Management, 2022)
The purpose of this research is to analyze the relationship between a company's strategic direction and the effectiveness of its service innovation and market presence. Owners and administrators were given a preliminary survey questionnaire to fill out. While correlation looks at the link between factors, regression demonstrates the null hypothesis. Customer focus, competitor focus, cost focus, inter-functional coordination, service innovation, and market success were all examined using various techniques. Our research showed that when looking at combined industries, only the link between client focus and service innovation is supported, while the link between service innovation and market performance is not. There is evidence to support the hypotheses that service innovation boosts market performance in the telecommunications sector, and that a focus on competitors and costs contributes to a more creative environment. While service innovation does support market performance in the food and beverage business, it does not support the relationship between cost orientation and inter-functional coordination. Few empirical investigations have focused on service innovation like this one. More research is needed to determine how a company's strategic direction affects its ability to innovate its products, but the findings of this study are transferable to other service industries.